Highly Dispersed CoO Embedded on Graphitized Ordered Mesoporous Carbon as an Effective Catalyst for Selective Fischer–Tropsch Synthesis of C5+ Hydrocarbons - Bai, Jirong; Song, Mingyao; Pang, Jiazheng; Wang, Lingling; Zhang, Jianping; Jiang, Xiankai; Ni, Zhijiang; Wang, Zhilei; Zhou, Quanfa (Frontiers in Chemistry, 2022)
Herein, we report the high Fisher-Tropsch synthesis performance of the Co-based catalysts supported on graphitized ordered mesoporous carbon (GMC-900) by using a facile strategy. Compared with CMK-3 and active carbon (AC), the obtained GMC-900 by using pollution-free soybean oil as carbon source exhibited enhanced catalytic performance after loading Co species due to its highly crystallized graphitic structure and uniform dispersion of CoO. As a result, the Co/GMC-900 was an effective catalyst with the maximum C5+ selectivity of 52.6%, which much outperformed Co/CMK-3 and Co/AC. This research provides an approach to produce advanced Co-based catalysts with satisfactory performances for efficient Fischer-Tropsch synthesis.